Adaptation, Validation and Reliability of the Online Sexual Experience Questionnaire (OSEQ) in University Students from Northern Peru (Journal SCIENCEVOLUTION, 2025)
The present study aimed to adapt, validate, and analyze the reliability of the Online Sexual Experience Questionnaire (OSEQ) in a sample of 517 university students from northern Peru. A quantitative instrumental study was conducted, with a basic and cross-sectional comparative design. An exploratory factor analysis (EFA) revealed a three-factor structure with adequate factor loadings, a KMO index of 0.875, and a statistically significant Bartlett’s test of sphericity (p < .001). Confirmatory factor analysis (CFA) confirmed the three-dimensional structure of the instrument with 11 items distributed across partner excitation (4 items), solitary excitation (3 items), and no excitation (4 items), showing satisfactory fit indices (CFI = 0.984, TLI = 0.978, RMSEA = 0.044). The instrument demonstrated high reliability, with a total McDonald's omega coefficient of 0.892 and dimensional values of 0.808, 0.928, and 0.909, respectively. The adapted version of the OSEQ was shown to have adequate psychometric properties in university students from northern Peru. Its factorial structure was validated, and high internal consistency was found, supporting the questionnaire as a valid and reliable tool for assessing online sexual behavior in this population.
Keywords: Cuestionario; OSEQ; Online Sexual Experience; Validity; Reliability